Adversity Quotient of Nursing Student - Rokayah, Cucu; Apriliani, Senny; Jayanti, Tri Nur; Puspitasari, Santi (Indonesian Journal of Global Health Research, 2023)
Achievement of student learning outcomes often encounter various obstacles to reach their achievements. Obstructions to accomplishment that are regularly confronted by understudies are need of certainty, passiveness to inquire questions, destitute time administration, delaying on tasks/work, diminished inspiration to memorize, the impact of awful companions, follow-up variables, and family/personal issues . Academic intelligence isn’t enough to provide readiness for students when facing academic failure. Therefore, Adversity Quotient (AQ) intelligence is needed to achieve successful learning. This study aims to determine the Adversity Quotient of Nursing Students. This type of research uses quantitative research, with a population of 494 nursing students, a sample of 221 students with stratified random sampling technique. Data collection techniques using the Adversity Response Profile questionnaire. Data analysis using frequency distribution. The results showed that 98% of the Adversity Quotient of Nursing Students were in the moderate AQ category (Camper). Based on the results of the research, it is advisable for the academic supervisor to provide intervention to students in the form of academic guidance or counseling to explore the potential of nursing students and optimize it.